2016
DOI: 10.4047/jap.2016.8.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength and micromorphologic analysis of surface-treated resin nanoceramics

Abstract: PURPOSEThe aim of this study was to evaluate the influence of different surface treatment methods on the microtensile bond strength of resin cement to resin nanoceramic (RNC).MATERIALS AND METHODSRNC onlays (Lava Ultimate) (n=30) were treated using air abrasion with and without a universal adhesive, or HF etching followed by a universal adhesive with and without a silane coupling agent, or tribological silica coating with and without a universal adhesive, and divided into 6 groups. Onlays were luted with resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 44 publications
2
40
1
5
Order By: Relevance
“…There are other studies that bring the chemical proportions of the porcelain with and without the presence of C, [62] as done in this study, or even report the obtained values and do not go in further details on the presence of this element [63]. Feldspathic VM9 porcelain, Enamic and Lava Ultimate chemical composition, obtained from XPS analyses, were consistent to previous studies [59,62,64,65] and showed agreement with the atomic proportions obtained in previous works [66][67][68][69].…”
Section: Discussionsupporting
confidence: 91%
“…There are other studies that bring the chemical proportions of the porcelain with and without the presence of C, [62] as done in this study, or even report the obtained values and do not go in further details on the presence of this element [63]. Feldspathic VM9 porcelain, Enamic and Lava Ultimate chemical composition, obtained from XPS analyses, were consistent to previous studies [59,62,64,65] and showed agreement with the atomic proportions obtained in previous works [66][67][68][69].…”
Section: Discussionsupporting
confidence: 91%
“…Seven different indirect substrates were considered in this review. These included lithium disilicate ceramic, 20,22,23,25,28‐39 yttrium‐stabilized zirconium dioxide ceramic, 20 ‐22, 24,27,32,37,40‐53 leucite‐reinforced ceramic, 20,54‐56 feldspathic porcelain, 32,59 polymer infiltrated ceramic material, 19,58 resin composite, 20,26,29,57,59‐66 and metal alloys 67–69 . The characteristics of these studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The bond strength between CRBs and resin cement is improved by surface treatments such as mechanical treatment and the application of adhesive material. Strong bonding between CRBs and resin cement depends on micromechanical interlocking and chemical bonding to the surface of the restorative material, which in turn requires cleaning and roughening for adequate surface activation 15) . However, previous studies indicate that alumina-blast flaws are similar in nature to true microcracks 12,[16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%